Comprehensive Report on Sweetpotato Breeding Network Meetings in East and Southern Africa 2024 - International Potato Center; CGIAR Initiative on Accelerated Breeding (2025)
The CGIAR-NARS Breeding Network serves as a pivotal collaboration platform, integrating the expertise of the CGIAR system with National Agricultural Research Systems (NARS) to develop and disseminate improved sweetpotato varieties across sub-Saharan Africa (SSA). This network operates through two sub-regional frameworks—the Southern Africa Sweetpotato Breeding Network (SAF) and the Eastern Africa Sweetpotato Breeding Network (EAF)—each addressing the unique agro-ecological and market requirements of their sub regions. In November 2024, the SAF and EAF networks convened separate meetings in Harare, Zimbabwe, and Kampala, Uganda, respectively, to evaluate breeding progress, refine priorities, and strengthen regional collaboration. The meetings brought together national breeding leads, representatives from CIP and ABI, and other stakeholders, with discussions revolving around breeding program assessments, cost the structure of breeding pipelines, alignment of regional, and national market segment, capacity-building needs, and infrastructure development.